Length-Weight Relationship And Condition Factor Of Village Pond-Reared Exotic Fish (Cyprinus Carpio Linnaeus, 1758) (Applied Biological Research, 2022)
The present study was aimed to assess the length-weight relationship and  condition factor of exotic common carp (Cyprinus carpio). The  morphological measures i.e., total length and weight of randomly selected  306 specimens of common carp, obtained from from Atgam village pond  Valsad (Gujarat), were measured in January 2021. The fish were divided  into four length groups i.e., A, B, C and D at length distance of 5.0 cm. The  result showed that the fish length and weight in population was in the range  d 205 to 259 g, respectively. The length frequency was 34, 79, 104 andthat lgroup C was dominant in the population, followed by group D, B and  A. The length and weight variables were positively correlated (r2 = 0.886)  and growth constant or regression coefficient was 2.804 revealing that the  growth ofish was negative allometric that was considered abnormal  growth as the weight increment was less with respect to fish length. The  mean value of condition factor for group A, B, C, D and pooled population  were 1.77 ± 0.03, 1.29 ± 0.01, 1.41 ± 0.02, 1.40 ± 0.01 and 1.41 ± 0.01, respectively, which indicated that the condition of fish was good in the  aquatic environment. The information generated may help in ecological and  biological management of fish for enhanced production and revenue  generation in village ponds.
Keywords: Cyprinus carpio; length-weight relationship; growth; condition factor